Beyond words - Ang, Julia Wei Lin (Nanyang Technological University, 2020)
Beyond Words follows the Ng family on their journey caring for their 13-year-old daughter Amelia, who has a rare degenerative condition. The film centers around the strong relationships that hold the family together, in particular Amelia’s bond with her older sister, Amanda. Amanda chose to be homeschooled to spend more time with Amelia, and also dedicates her time to advocating for those with special needs and their siblings.